Engaging Supply Chains in Climate Change - Jira, Chonnikarn (Fern); Toffel, Michael W. (Manufacturing and Service Operations Management, 2013)
Suppliers are increasingly being asked to share information about their vulnerability to climate change and their strategies to reduce greenhouse gas emissions. Their responses vary widely. We theorize and empirically identify several factors associated with suppliers being especially willing to share this information with buyers, focusing on attributes of the buyers seeking this information and of the suppliers being asked to provide it. We test our hypotheses using data from the Carbon Disclosure Project's Supply Chain Program, a collaboration of multinational corporations requesting such information from thousands of suppliers in 49 countries. We find evidence that suppliers are more likely to share this information when requests from buyers are more prevalent, when buyers appear committed to using the information, when suppliers belong to more profitable industries, and when suppliers are located in countries with greenhouse gas regulations. We find evidence that these factors also influence the comprehensiveness of the information suppliers share and their willingness to share the information publicly.